Characterization of Genetic Diversity in Accessions of Prunus salicina Lindl: Keeping fruit flesh color ideotype while adapting to water stressed environments - Acuña, Cintia Vanesa (2019)
The genetic diversity of 14 Japanese plum (Prunus salicina Lindl) landraces adapted to an ecosystem of alternating flooding and dry conditions was characterized using neutral simple sequence repeat (SSR) markers. Twelve SSRs located in six chromosomes of the Prunus persica reference genome resulted to be polymorphic, thus allowing identification of all the evaluated landraces. Differentiation between individuals was moderate to high (average shared allele distance (DAS) = 0.64), whereas the genetic diversity was high (average indices polymorphism information content (PIC) = 0.62, observed heterozygosity (Ho) = 0.51, unbiased expected heterozygosity (uHe) = 0.70). Clustering and genetic structure approaches grouped all individuals into two major groups that correlated with flesh color. This finding suggests that the intuitive breeding practices of growers tended to select plum trees according to specific phenotypic traits. These neutral markers were adequate for population genetic studies and cultivar identification. Furthermore, we assessed the SSR flanking genome regions (25 kb) in silico to search for candidate genes related to stress resistance or associated with other agronomic traits of interest. Interestingly, at least 26 of the 118 detected genes seem to be related to fruit quality, plant development, and stress resistance. This study suggests that the molecular characterization of specific landraces of Japanese plum that have been adapted to extreme agroecosystems is a useful approach to localize candidate genes which are potentially interesting for breeding.